2013
DOI: 10.1590/s1415-43662013001200015
|View full text |Cite
|
Sign up to set email alerts
|

Conforto e estresse térmico em ovinos no Norte da Bahia

Abstract: RESUMOO clima é fator determinante para o sucesso da atividade produtiva; logo, a interação animal x clima deve ser considerada visando a uma eficiência maior na exploração pecuária, de vez que os animais apresentam diferentes respostas às peculiaridades do clima de cada região. Neste trabalho objetivou-se avaliar o conforto térmico de ovinos das raças Santa Inês, Dorper e Sem Raça Definida -SRD, criados a céu aberto. A pesquisa foi conduzida no Campus III da Universidade do Estado da Bahia, em Juazeiro, no pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
4
0
4
Order By: Relevance
“…Leitão et al (2013) found ITGU values above 94 when keeping Santa Inês sheep in paddocks deprived of coverage in Juazeiro, BA, Brazil, in the dry period, concluding that the existence of a cover can have a significant effect on the reduction of the stress condition for sheep raised in the semiarid. This fact was corroborated by the present research since a reduction of up to 10% in the BGHI value between the two environments was found.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Leitão et al (2013) found ITGU values above 94 when keeping Santa Inês sheep in paddocks deprived of coverage in Juazeiro, BA, Brazil, in the dry period, concluding that the existence of a cover can have a significant effect on the reduction of the stress condition for sheep raised in the semiarid. This fact was corroborated by the present research since a reduction of up to 10% in the BGHI value between the two environments was found.…”
Section: Resultsmentioning
confidence: 93%
“…Santos et al (2011) reported that in this region, most sheep are raised in pastures with little or no shade and analyzing the effect of shading on the comfort of Santa Inês sheep, showed that the shade provided by the trees reduced the radiant heat load by up to 44.7%, providing a better thermal environment for the animals. Relative to the comfort of sheep Santa Inês, Neves et al High BGHI values in the semi-arid region are also cited by and Leitão et al (2013).…”
Section: Introductionmentioning
confidence: 96%
“…Já Silva Sobrinho (2001), especifica que para ovinos deslanados, como os da raça Santa Inês, a zona de conforto de 5°C para temperatura crítica inferior, e de 45°C para a superior. De acordo com Leitão et al (2013), o período da tarde é quando os ovinos mais são submetidos a situação de alerta em relação ao estresse térmico.…”
Section: Zona De Conforto Térmico Para Ovinosunclassified
“…Desta forma, armazena maior quantidade de energia térmica do que um de coloração clara, que apresenta maior refletividade como afirmam Veríssimo et al (2009) ao analisar a tolerância ao calor em ovelhas da raça Santa Inês. Leitão et al (2013) avaliaram o conforto térmico de ovinos das raças Santa Inês, Dorper e Sem Raça Definida (SRD), criados a céu aberto em temperatura ambiente máxima de 36,9°C e mínima de 22,9 °C constataram que a temperatura da superfície da pele no lado ensolarado do flanco no período da manhã foi de 39,9 °C e 43,8 °C e ao meio dia (12 h) foi de 45,9 °C e 49,7 °C para os animais de pelames branco e preto respectivamente, não diferindo entre si. Para o lado sombreado do flanco do animal, a temperatura da superfície da pele foi de 37,0 °C e 38,6 °C no período da manhã, e às 12 h de 43,8 °C e 45,3 °C para os pelames branco e preto, respectivamente, onde esta última cor diferiu estatisticamente entre si.…”
Section: Coloração Do Pelame E Da Peleunclassified
“…Sheep farming is an activity of great social and economic importance in Brazil. It represents a good alternative for Brazilian agribusiness (LEITÃO et al, 2013). Despite the increase in production and consumption of the products from the sheep industry in the country, when compared on a world scale, the production rates are still low.…”
Section: Introductionmentioning
confidence: 99%